Pengaruh Edukasi Pencegahan COVID-19 terhadap Peningkatan Pengetahuan dan Sikap Cuci Tangan pada Siswa di SMK Muhammadiyah Kartasura - Kirana, Sahasika Apta; Suswardany, Dwi Linna (Poltekkes Kemenkes Kendari, 2023)
SARS-CoV-2 or COVID-19 is transmitted through close contact exposure or direct transmission from asymptomatic, asymptomatic, or symptomatic individuals who contain the virus. So preventive measures are needed, such as washing hands properly. Hand hygiene is a barrier to transmission through objects or materials that allows transmission with a lower risk. The research method used is quantitative with a quasi-experimental type of research. In the research, a pretest and posttest were carried out to determine the extent of knowledge and attitudes before and after being given education. There is an influence on the results of the Wilcoxon test with a p-value in the pre-test of 0.009 < 0.05 and in the post-test so that there is an influence of hand washing education using the lecture method on knowledge, Covid-19 prevention education using the lecture method which is based on national defense has an influence on increasing hand washing attitudes in Muhammadiyah Vocational School students with a p-value of 0.037 < 0.05. The results of the research showed that there was a change in the knowledge and attitude values of Muhammadiyah Kartasura Vocational School students so the education provided had an influence on the knowledge and attitudes of Kartasura Muhammadiyah Vocational School students.